Kohesi Gramatikal Pada Kumpulan Puisi Geladi Diri Dan Implikasinya Dalam Pembelajaran Bahasa Di SMP - Romadhani, Ika Merry; , Drs. Andi Haris Prabawa, M.Hum (2016)
This study aimed to describe the grammatical cohesion in a collection of poems GeladiDiri, describes the implications of the results of research in learning Indonesian in junior high school. Collecting data using documentation engineering and technical notes. The method used to analyze data is unified referential intralingual subtype with advanced engineering techniques Pilah Element Qualifier (PUP), and constant comparison analysis techniques. Based on the research results, there are two conclusions: the results of research on grammatical cohesion in a collection of poems GeladiDiri namely that the reference (reference) is composed of a single form that the reference persona I free me, tied closely - left, my right closely bound form, the plural form of our free and we , this reference a single persona II left you- closely bound form, the form closely bound thy right, his right closely bound form, this reference their plural persona III; this reference that the reference demonstrative demonstrative consists of a place in your lap on your lips, this, on the road, in the lap of his mother, here, there, everywhere, this reference demonstrative July time, past, present; such that the reference comparative, like; (2) substitution (substitution) consists of a nominal substitution state with the 'motherland', the country with the 'motherland', criminals with criminals, verbal substitution made by 'painting', struggling with the 'screaming'; (3) deletion (ellipsis) mother's father, country, youth, heart, i; (4) the coupling (conjunction) consisting of conjunctions contention but, but, but, instead of excess conjunctions, conjunctions konsesif though, though, conjunctions additions (additives) and, conjunction or choice. The results of this study can be implicated in learning Indonesian in junior high school. Grammatical cohesion raised in Indonesian language learning in junior high school grade levels VII and VIII by linking SK and KD. Keyword: grammatical cohesion, poetry, learning.